12-month follow-up of an exploratory 'brief intervention' for high-frequency cannabis users among Canadian university students - Fischer Benedikt; Jones Wayne; Shuper Paul; Rehm Jürgen (BMC, 2012)
Abstract Background One in three young people use cannabis in Canada. Cannabis use can be associated with a variety of health problems which occur primarily among intensive/frequent users. Availability and effectiveness of conventional treatment for cannabis use is limited. While Brief Interventions (BIs) have been shown to result in short-term reductions of cannabis use risks or problems, few studies have assessed their longer-term effects. The present study examined 12-month follow-up outcomes for BIs in a cohort of young Canadian high-frequency cannabis users where select short-term effects (3 months) had previously been assessed and demonstrated. Findings N = 134 frequent cannabis users were recruited from among university students in Toronto, randomized to either an oral or a written cannabis BI, or corresponding health controls, and assessed in-person at baseline, 3-months, and 12-months. N = 72 (54 %) of the original sample were retained for follow-up analyses at 12-months where reductions in 'deep inhalation/breathholding' (Q = 13.1; p < .05) and 'driving after cannabis use' (Q = 9.3; p < .05) were observed in the experimental groups. Reductions for these indicators had been shown at 3-months in the experimental groups; these reductions were maintained over the year. Other indicators assessed remained overall stable in both experimental and control groups. Conclusions The results confirm findings from select other studies indicating the potential for longer-term and sustained risk reduction effects of BIs for cannabis use. While further research is needed on the long-term effects of BIs, these may be a valuable - and efficient - intervention tool in a public health approach to high-risk cannabis use.